Preparation of a biomimetic superomniphobic hierarchical structure and analysis of droplet wettability. Issue 2 (18th May 2022) - Li, Jing; Feng, Qunxiang; Guo, Nan; Wang, Fei; Du, Xin; Du, Feng
Abstract: In this study, a bioinspired hierarchical structure was formed with superomniphobicity on a 7075 aluminium alloy using laser ablation. The morphology and wetting characteristics of the biomimetic sample surface were characterised using scanning electron microscopy, laser confocal microscopy, and contact angle measurements. The effect of the liquid properties and surface structures on the rolling behaviour was investigated. The results suggest that the fabricated biomimetic sample surface was a hierarchical structure. The prepared sample had superomniphobicity and low adhesion properties, and the contact angles of six different liquid droplets on the sample surface reached or approached 150°. Specifically, the largest contact angle was 152°, and the average rolling angle was 7.7°. This multi‐hydrophobic surface provides a valuable reference for the research study and use of a variety of solid–liquid contacts.